PENGARUH PENAMBAHAN ZEOLIT DAN TRICHODERMA SP. TERHADAP KUALITAS PUPUK ORGANIK DARI KOTORAN AYAM - Widigdyo, Anang; Kurniawan, David; Utama, Adiguna Sasama Wahyu; Kurniawan, H. (Jurnal Sains dan Teknologi Industri Peternakan, 2022)
The purpose of this study was to determine the effect of the addition of zeolite and Trichoderma S.p on the quality of organic fertilizer from chicken manure. This study used an experimental method with 4 treatments: P0, control treatment; P1, Fecal Fermentation (FF) with 5% zeolite; P2, FF with zeoilt 7.5%; P3, FF with 10% zeolite. Observational analysis was carried out at the Fertilizer Testing Laboratory of the Blitar Regency Agriculture Service which included parameters of C-organic levels, NPK levels. The results showed that the value of C-Organic and N,P,K levels of fermented fertilizer added with Zeolite still met the SNI threshold on the manufacture of organic fertilizer from poultry manure. The highest results were obtained in the P3 treatment with a higher organic C-value than the control P0 treatment. Meanwhile, the highest total N, P, K levels were the control treatment P0. Based on the results of observational data, research has shown that the addition of zeolite in the manufacture of organic fertilizer from chicken manure can increase the value of macro-nutrient content which can increase soil fertility and prevent soil degradation.